Five-year prospective fistula audit in a single center. TIG training negates consultant learning curve, but surgeons should beware the mid-range palatal defect. Issue 2 (February 2022) - Maciver, Rory; Baniulyte, Gabriele; O'Neill, Tomas B.; McAllister, Peter; Drake, David; Russell, Craig; Devlin, Mark F.
Summary: The aim of primary palatoplasty is to achieve optimum speech with minimal morbidity. Symptomatic fistulae are well-recognised complications of palatoplasty and may require additional surgical intervention, increasing the burden of care. Our aims were to better understand fistula experience in our unit and compare fistula rates between an established consultant and a newly appointed training interface group (TIG) trained consultant. Post-operative fistulae were prospectively and independently recorded by Cleft Clinical Nurse Specialists as part of routine 6-week post-operative reviews. Cleft type and intra-operative hard-soft palate junction (HSPJ) width were prospectively recorded by operating surgeons. Data were collated and analysed using Microsoft Excel. Between 1 January 2014 and 31 December 2018, 250 primary palatoplasties were performed. The overall fistula rate was 8% (0% SMCP, ICP 7%, UCLP 8%, BCLP 22%). Fistulae clustered in clefts with a mid-range HSPJ width of 12–16 mm. Numerically, fistula rates remained similar over time despite increased unit activity (doubling of primary surgeries in 2017 and 2018). There was no significant difference in fistulae rates between surgeons ( P > 0.05). Overall fistulae rate compared favourably with published data. TIG fellowships were designed in the context of cleft surgery to address issues relating to steep operative learning curves. These data demonstrate that results from a newly appointed TIG-trained surgeon are comparable to that of an established TIG-trained surgeon. Data also suggest surgeons should be aware of the risk of fistulae in the mid-range palatal defect and in HSPJ widths of 12–16 mm.